Anti-PD-1/PD-L1 antibody therapy for pretreated advanced nonsmall-cell lung cancer: A meta-analysis of randomized clinical trials. Issue 35 (August 2016) - Zhou, Guo-Wu; Xiong, Ye; Chen, Si; Xia, Fan; Li, Qiang; Hu, Jia
Abstract: Background: Anti-PD-1/PD-L1 antibody therapy is a promising clinical treatment for nonsmall-cell lung cancer (NSCLC). However, whether anti-PD-1/PD-L1 antibody therapy can provide added benefits for heavily pretreated patients with advanced NSCLC and whether the efficacy of anti-PD-1/PD-L1 antibody therapy relates to the tumor PD-L1 expression level remain controversial. Thus, this meta-analysis evaluated the efficacy and safety of anti-PD-1/PD-L1 antibody therapy for pretreated patients with advanced NSCLC. Methods: Randomized clinical trials were retrieved by searching the PubMed, EMBASE, ASCO meeting abstract, clinicaltrial.gov, and Cochrane library databases. The pooled hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), and odds ratios for the overall response rate and adverse events (AEs) were calculated by STATA software. Results: Three randomized clinical trials involving 1141 pretreated patients with advanced NSCLC were included. These trials all compared the efficacy and safety of anti-PD-1/PD-L1 antibodies (nivolumab and MPDL3280A) with docetaxel. The results suggested that, for all patients, anti-PD-1/PD-L1 therapy could acquire a greater overall response (odds ratio = 1.50, 95% CI: 1.08–2.07, P  = 0.015, P for heterogeneity [ P h ] = 0.620) and longer OS (HR = 0.71, 95% CI: 0.61–0.81, P  < 0.001, P h  = 0.361) than docetaxel, but not PFS (HR = 0.83, 95% CI: 0.65–1.06, P  = 0.134; P h  = 0.031). Subgroup analyses according to the tumor PD-L1 expression level showed that anti-PD-1/PD-L1 therapy could significantly improve both OS and PFS in patients with high expressions of PD-L1, but not in those with low expressions. Generally, the rates of grade 3 or 4 AEs of anti-PD-1/PD-L1 therapy were significantly lower than that of docetaxel. However, the risks of pneumonitis and hypothyroidism were significantly higher. Conclusion: Anti-PD-1/PD-L1 antibody therapy may significantly improve the outcomes for pretreated advanced NSCLC patients, with a better safety profile than docetaxel.